PENINGKATAN MOTIVASI BELAJAR SISWA KELAS IV MELALUI PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) DENGAN MEDIA WORDWALL PADA MATA PELAJARAN IPAS DI SD AL ISLAM 1 SURAKARTA - Karomatul Sabani; Lulux Novitasari; Syifa Putri Maulidya; Puspita Indra Wardhani; Indah Nadia Mayasari (Jurnal Genta Mulia, 2025)
Using appropriate learning media will make learning interesting and not monotonous, thereby increasing students' learning motivation. This research aims to determine the effectiveness of learning using the Teams Games Tournament (TGT) learning model assisted by Wordwall media on students' science learning motivation. The subjects of this research were 19 students in class IV-A of SD Al Islam 1 Surakarta. The method used is Classroom Action Research (PTK) with data collection through observation, interviews and learning motivation questionnaires. The research results showed an increase in student learning motivation in each cycle. In the pre-cycle, the percentage of learning motivation reached 61.3%. After implementing the Teams Games Tournament (TGT) learning model assisted by Wordwall in cycle I, student learning motivation increased to 73%. Then in cycle II it increased to 80.1%. So, it can be concluded that the use of the Teams Games Tournament (TGT) learning model assisted by Wordwall can increase the learning motivation of class IV-A students at SD I Al-Islam Surakarta in the science subject.